Moderate Da'wah and National Resilience: A Case Study at MUI Kab. Bandung - Dindin Solahudin (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2023)
This study tries to offer constructive preaching to build national resilience by highlighting Islamic moderation (wasaṭiyyatul Islam) through a series of moderate preaching. The method used in this paper is a literature review. Wasaṭiyyatul Islām is an authentic character of Islamic law which reflects i'tidāl (perpendicularity) and istiqāmah (consistency) on aṣ-ṣirāth al-mustaqīm (straight path). Islam is moderate in character as long as it is understood in the corridor of truth. Islam, with its wasaṭiyyah character, should also be preached reasonably. Muqābalah moderation is not radicalism but extremity. Radical da'wah is not a problem as long as istiqāmah is in the corridor of moderation. Preaching radically moderate Islam is certainly not justified. Extreme da'wah undermines Islamic moderation and contradicts Islamic law itself. Islamic moderation necessitates its adherents to practice Islamic law reasonably. Moderate da'wah socializes Islam to be practised by its followers reasonably. Religious moderation is an essential social capital for national resilience